Exploring Tangible Factors Influencing the Choice of Physiotherapy Services - Zidni Imanurrohmah Lubis; Septy Kumalasari; Sri Sunaringsih Ika Wardojo (GLOBAL HEALTH SCIENCE GROUP, 2025)
Physical evidence (tangibles) encompasses various aspects such as physical facilities, equipment, and the appearance of personnel, all of which serve as indicators of healthcare service quality and influence patients' choices when selecting healthcare facilities. In the context of physiotherapy services, patient satisfaction often arises from their experiences and perceptions of these tangible elements. Specifically, physical evidence plays a critical role in shaping the quality of service, thereby affecting patient satisfaction levels. This relationship underscores the significance of tangible factors in assessing the overall quality of healthcare services and their impact on patient experiences. This study aims to investigate the relationship between the factors of physical evidence (tangibles) and the selection of physiotherapy services in Malang City. This research employs an analytical observational design with a cross-sectional approach. The study population consists of residents of Malang City, with a sample size of 105 respondents selected through purposive sampling techniques. The results of the Chi-Square test revealed a significant value of 0.026 (p < 0.05), indicating a relationship between the factors of physical evidence (tangibles) and the selection of physiotherapy services in Malang City. There exists a relationship between the factors of physical evidence (tangibles) and the selection of physiotherapy services in Malang City.